PENGARUH KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN PUSKESMAS KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Nurlina Anggraeni; Sapri Sapri; Rifni Nikmat Syarifuddin (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the Health Service Quality of Panca Rijang Health Center, Sidenreng Rappang and to out the Patient Statisfaction of Panca Rijang Health Center in Sidenreng Rappang and the Effect of Quality of Health Service on Patient Satisfaction in Panca Rijang Health Center, Sidenreng Rappang. The population of this study was all outpatient referral patients and outpatient visit at the Panca Rijang District Public Health Center, namely 2114 people. The sample used by researchers was 95.48 or 95 respondents, taken based on insedental sampling techniques. This type of research is descriptive qualitative. Data collection techniques used in this study are observation, questionnaire, interview and library study. The collected data is then used by means of data analysis techniques, using SPSS 16.0 for Windows and the Likert Scale. The results of this study indicate that the quality of health service at the subdistrict health center in the five district of Panca Rijang district Sidenreng Rappang with a recapitulation of 58,12% categorized as not good. Satisfaction of patiens in the district health center Panca Rijang regency Sidenreng Rappang with a recapitulation of 63,2% categorized as good, however, it is know that there is a problem with the location indicator 60,4% facility 57%, image 60%. Effect of Quality of Health Service on Patienst Satisfaction in Panca Rijang District Health Center, Sidenreng Rappang Districtwith a value of thitung ≥ ttabel 1.740 ≥ 1.661, then Ho is rejected and Ha is accepted, meaning that it is significant.